Nocturnal Risks-High Bat Activity in the Agricultural Landscape Indicates Potential Pesticide Exposure - Stahlschmidt, Peter; Hahn, Melanie; Brühl, Carsten A. (Frontiers in Environmental Science, 2017)
Although agriculture dominates much of Europe's landscape, there is virtually no information on foraging activity of bats in different crops. Additionally little is known about pesticide exposure of bats and related effects and there are currently no specific regulatory requirements to include bats in European Union pesticide risk assessments for the registration of these chemicals although other mammals are considered. To evaluate the potential pesticide exposure of bats, we studied bat diversity and activity as well as the availability of aerial prey insects in different crops and semi-natural habitats in south-western Germany in a landscape dominated by agriculture. In 300 accumulated sampling nights more than 24,000 bat call sequences were acoustically recorded and, in parallel, almost 110,000 insects of suitable prey sizes were sampled by light traps. A total of 14 bat species were recorded, among them the locally rare and for Germany critically endangered northern bat (Eptesicus nilssonii) and the barbastelle (Barbastella barbastellum), all of them also occurring over agricultural fields. In comparison to agricultural habitats, higher activity levels in forest sites were only found for Myotis species but not for species of the genera Pipistrellus, Eptesicus and Nyctalus. There were no significant differences in the availability of aerial nocturnal insects between forest, meadow and agricultural habitats. Comparing the different agricultural crops, significantly fewer bat call sequences and lower numbers of nocturnal insects were collected above the vineyards compared to orchards, cereal and vegetable fields. Highest activity levels of all bat species were recorded above agricultural fields situated next to forests. Given the high bat activity levels recorded at several agricultural sites, among them orchard and vegetable fields both known for their high pesticide inputs, and the availability of suitable prey insects, we conclude that pesticide exposure via ingestion of contaminated insect prey is possible. This potential risk is currently not considered in the European pesticide risk assessment scheme.